Mathematics Education Students' Experiences during Lockdown: Managing Collaboration in eLearning - Nigel Calder; Mairaj Jafri; Lina Guo (MDPI AG, 2021)
The current world crisis of COVID-19 has enforced international lockdowns in educational institutions, necessitating that these institutions quickly transition to online learning. In mathematics education studies, where collaborative problem-solving is considered a necessary pedagogical approach, lecturers have had challenges incorporating collaborative problem-solving in an authentic manner. There are now also complex living and learning contexts in which the students have to undertake their learning processes. This paper examines students' experiences of the rapid transition to online learning and their perceptions of the advantages and barriers that ensued. A small comparative case study was used to explore the complexity of the situation, within rich, authentic settings. Questionnaires and semi-structured interviews were used. The participants found that personal circumstances related to having children and partners at home while they studied, and aspects such as not interacting directly with other students to clarify and mediate their thinking, led to major initial frustrations with collaborating. While some of these continued throughout lockdown they did adjust and recognize that the advantages, such as a mix of formal and informal digital pedagogical media, gave them greater flexibility and led to deeper reflective thinking. We contend that some elements related to the adaptions made should become permanent features of face-to-face learning.